PERAN POLA ASUH BAGI ANAK TERLANTAR DI PANTI SOSIAL ASUHAN ANAK (PSAA) HARAPAN MAJELUK KOTA MATARAM NTB - Abdul Najib; Rosita Wardiana (KOMUNITAS, 2017)
Parenting for children is a highly transcendental thing in creating a young generation who has a mandate in social change. Children are the successors who will continue the leadership in the future. The existence of parenting is a behavioral pattern applied to children which is relatively consistent over time and is very influential in the formation of characteristics of children which the impact will be felt by the children either in aspect of positive or negative. Caregivers have a very big responsibility because the success of foster children is very dependent on coaching of caregivers. Therefore, the caregivers can act as a parent in giving the attention, affection and security, brothers in communicating with the children can solve the problems, the teachers in helping to learn, the service in helping to meet the needs of the children. Caregivers are people who play all roles of the orphanage to educate and direct the foster children. The orphanage environment collaborates with community and school teachers where the foster children attend school. Caregivers through foster parents are temporary, where the children must be immediately returned to the care of their parents. In carrying out its role as a caregiver, the social orphan age of children (PSAA) of Harapan Majeluk of Mataram does its job with patience and compassion, because besides acting as a caregiver, caregivers of socialorphanage of children(PSAA) of Harapan Majeluk of Mataram also roles as teachers.Keywords: Roles, Parenting, Waifs.